Chlorpromazine versus atypical antipsychotic drugs for schizophrenia - Saha, Kumar B (Cochrane Database Syst Rev, 2016)
BACKGROUND: Chlorpromazine is an aliphatic phenothiazine, which is one of the widely‐used typical antipsychotic drugs. Chlorpromazine is reliable for its efficacy and one of the most tested first generation antipsychotic drugs. It has been used as a ‘gold standard’ to compare the efficacy of older and newer antipsychotic drugs. Expensive new generation drugs are heavily marketed worldwide as a better treatment for schizophrenia, but this may not be the case and an unnecessary drain on very limited resources. OBJECTIVES: To compare the effects of chlorpromazine with atypical or second generation antipsychotic drugs, for the treatment of people with schizophrenia. SEARCH METHODS: We searched the Cochrane Schizophrenia Group's Trials Register up to 23 September 2013. SELECTION CRITERIA: We included randomised controlled trials (RCTs) that compared chlorpromazine with any other atypical antipsychotic drugs for treating people with schizophrenia. Adults (as defined in each trial) diagnosed with schizophrenia, including schizophreniform, schizoaffective and delusional disorders were included in this review. DATA COLLECTION AND ANALYSIS: At least two review authors independently screened the articles identified in the literature search against the inclusion criteria and extracted data from included trials. For homogeneous dichotomous data, we calculated the risk ratio (RR) and the 95% confidence intervals (CIs). For continuous data, we determined the mean difference (MD) values and 95% CIs. We assessed the risk of bias in included studies and rated the quality of the evidence using the GRADE approach. MAIN RESULTS: This review includes 71 studies comparing chlorpromazine to olanzapine, risperidone or quetiapine. None of the included trials reported any data on economic costs. 1. Chlorpromazine versus olanzapine In the short term, there appeared to be a significantly greater clinical response (as defined in each study) in people receiving olanzapine (3 RCTs, N = 204; RR 2.34, 95% CI 1.37 to 3.99, low quality evidence). There was no difference between drugs for relapse (1 RCT, N = 70; RR 1.5, 95% CI 0.46 to 4.86, very low quality evidence), nor in average endpoint score using the Brief Psychiatric Rating Scale (BPRS) for mental state (4 RCTs, N = 245; MD 3.21, 95% CI −0.62 to 7.05,very low quality evidence). There were significantly more extrapyramidal symptoms experienced amongst people receiving chlorpromazine (2 RCTs, N = 298; RR 34.47, 95% CI 4.79 to 248.30,very low quality evidence). Quality of life ratings using the general quality of life interview (GQOLI) ‐ physical health subscale were more favourable with people receiving olanzapine (1 RCT, N = 61; MD −10.10, 95% CI −13.93 to −6.27, very low quality evidence). There was no difference between groups for people leaving the studies early (3 RCTs, N = 139; RR 1.69, 95% CI 0.45 to 6.40, very low quality evidence). 2. Chlorpromazine versus risperidone In the short term, there appeared to be no difference in clinical response (as defined in each study) between chlorpromazine or risperidone (7 RCTs, N = 475; RR 0.84, 95% CI 0.53 to 1.34, low quality of evidence), nor in average endpoint score using the BPRS for mental state 4 RCTs, N = 247; MD 0.90, 95% CI −3.49 to 5.28, very low quality evidence), or any observed extrapyramidal adverse effects (3 RCTs, N = 235; RR 1.7, 95% CI 0.85 to 3.40,very low quality evidence). Quality of life ratings using the QOL scale were significantly more favourable with people receiving risperidone (1 RCT, N = 100; MD −14.2, 95% CI −20.50 to −7.90, very low quality evidence). There was no difference between groups for people leaving the studies early (one RCT, N = 41; RR 0.21, 95% CI 0.01 to 4.11, very low quality evidence). 3. Chlorpromazine versus quetiapine In the short term, there appeared to be no difference in clinical response (as defined in each study) between chlorpromazine or quetiapine (28 RCTs, N = 3241; RR 0.93, 95% CI 0.81 to 1.06, moderate quality evidence) nor in average endpoint score using the BPRS for mental state (6 RCTs, N = 548; MD −0.18, 95% CI −1.23 to 0.88, very low quality evidence). Quality of life ratings using the GQOL1‐74 scale were significantly more favourable with people receiving quetiapine (1 RCT, N = 59; MD −6.49, 95% CI −11.30 to −1.68, very low quality evidence). Significantly more people receiving chlorpromazine experienced extrapyramidal adverse effects (8 RCTs, N = 644; RR 8.03, 95% CI 4.78 to 13.51, low quality of evidence). There was no difference between groups for people leaving the studies early in the short term (12 RCTs, N = 1223; RR 1.04, 95% CI 0.77 to 1.41,moderate quality evidence). AUTHORS' CONCLUSIONS: Most included trials included inpatients from hospitals in China. Therefore the results of this Cochrane review are more applicable to the Chinese population. Mostincluded trials were short term studies, therefore we cannot comment on the medium and long term use of chlorpromazine compared to atypical antipsychotics. Low qualityy evidence suggests chlorpromazine causes more extrapyramidal adverse effects. However, all studiesused varying dose ranges, and higher doses would be expected to be associated with more adverse events.